Endovascular Recanalization and Angioplasty of a Lengthy, 25 Years Old Superficial Femoral Artery Occlusion - Florian Lüders; Alfred Doku; Nasser Malyar; Holger Reinecke (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2014)
Introduction: Often physicians and patients believe that occluded vessels could not be recanalized because an occlusive lesion is too long or exists over a very long period. We report a successful recanalization of a lengthy, quarter-century old superficial femoral artery occlusion through a percutaneous transluminal angioplasty. Report: We present the recanalization and angioplasty of the superficial femoral artery in a patient with a 37 cm long and 25 years old superficial femoral artery occlusion with limb ischemia, and who was considered as a high surgical risk. Through a subintimal dissection plane and with subsequent Pacific-balloon dilatation, two stent grafts were deployed to maintain patency. The post-intervention angiography and ankle-brachial index (ABI) showed a satisfactory primary outcome. Discussion: The recent guidelines recommend the endovascular therapy as the preferred strategy in patients with long and complex femoropopliteal lesions, an adequate recommendation as our case demonstrates. This case demonstrates that neither lesion length nor duration of an occlusion should be a cause to withhold an endovascular treatment.